2018
DOI: 10.1097/ogx.0000000000000512
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Screening With the Validated Opioid Risk Tool Demonstrates Gynecologic Oncology Patients Are at Low Risk for Opioid Misuse

Abstract: (Abstracted from Gynecol Oncol 2017;147:456–459) Mortality rates in the United States due to opioid misuse have risen in recent years and continue to rise. Many of these deaths were attributed to misuse of prescription drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…The grey literature search did not yield any results that met our study eligibility criteria. We contacted authors of 13 studies [53][54][55][56][57][58][59][68][69][70][71][72][73] and received responses from six authors, 54,55,[69][70][71][72] who provided additional data for four studies. 54,55,69,72 We identified two types of tools used to assess for problematic opioid use in palliative care: questionnaires (n = 32, 76%) [53][54][55]57,58,[61][62][63]65,66, and urine drug tests (n = 21, 50%), 17,53,55,56,57,59,60,63,64,67,68,70,71,81,82,85,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The grey literature search did not yield any results that met our study eligibility criteria. We contacted authors of 13 studies [53][54][55][56][57][58][59][68][69][70][71][72][73] and received responses from six authors, 54,55,[69][70][71][72] who provided additional data for four studies. 54,55,69,72 We identified two types of tools used to assess for problematic opioid use in palliative care: questionnaires (n = 32, 76%) [53][54][55]57,58,[61][62][63]65,66, and urine drug tests (n = 21, 50%), 17,53,55,56,57,59,60,63,64,67,68,70,71,81,82,85,…”
Section: Resultsmentioning
confidence: 99%
“…53,54,57,58,61,71,72,73,85 Previous attempts had been made to validate this tool as a measure of problematic opioid use in chronic non-cancer pain (Supplemental Appendix D). Our included studies reportedly used the ORT to assess for the following constructs in palliative care: opioid abuse, 54,58,61,73 dependence, 69 misuse, 53,54,57,58,72,73,85 diversion, 54 aberrant behaviors, [71][72][73] and safety. 53,57 Three studies used the ORT to measure general substance abuse 71 and misuse (Table 3).…”
Section: Cut Down Annoyed Guilty and Eye-opener (Cage)mentioning
confidence: 99%
“…However, more recent studies have reported that the rate of opioid addiction or aberrant behavior is increasing in this patient population. The prevalence of OAB was reported as low as 7.7% and as high as 43% in these more recent studies [10][11][12][13][14]22]. Thus, it is likely that the overall prevalence of OAB in cancer patients is no longer low.…”
Section: Discussionmentioning
confidence: 99%
“…The original study presented no information about the primary diagnosis of the subjects. In cancer patients, the risk of OAB has been reported to vary considerably, from 10% to 40% [10][11][12][13][14]. In a study comparing ORT of cancer patients and heart failure patients, the proportion of moderate-to highrisk patients was higher in cancer patients (39% versus 23%), although the difference was not statistically signi cant [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation